2007
DOI: 10.1101/gr.5623407
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor binding and modified histones in human bidirectional promoters

Abstract: Bidirectional promoters have received considerable attention because of their ability to regulate two downstream genes (divergent genes). They are also highly abundant, directing the transcription of ∼11% of genes in the human genome. We categorized the presence of DNA sequence motifs, binding of transcription factors, and modified histones as overrepresented, shared, or underrepresented in bidirectional promoters with respect to unidirectional promoters. We found that a small set of motifs, including GABPA, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
140
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(153 citation statements)
references
References 48 publications
13
140
0
Order By: Relevance
“…In bidirectional promoters, the boxes were found above chance. This finding is in agreement with a study using chromatin-immunoprecipitation (ChIP) on 118 regions in the human genome that showed that CCAAT boxes, among a few other small motifs, are over-represented in bidirectional promoters, in comparison to unidirectional ones (Lin et al, 2007). Interestingly, our analysis of a much larger set of promoters further shows that in unidirectional promoters, the boxes are also found above chance, provided that they have a low number of mismatches from consensus.…”
Section: Nf-y Type Ccaat Box Occurrencesupporting
confidence: 92%
See 1 more Smart Citation
“…In bidirectional promoters, the boxes were found above chance. This finding is in agreement with a study using chromatin-immunoprecipitation (ChIP) on 118 regions in the human genome that showed that CCAAT boxes, among a few other small motifs, are over-represented in bidirectional promoters, in comparison to unidirectional ones (Lin et al, 2007). Interestingly, our analysis of a much larger set of promoters further shows that in unidirectional promoters, the boxes are also found above chance, provided that they have a low number of mismatches from consensus.…”
Section: Nf-y Type Ccaat Box Occurrencesupporting
confidence: 92%
“…Previous studies suggest that NF-Y type CCAAT boxes are common regulators of bidirectional mammalian promoters (Lin et al, 2007;Zanotto et al, 2009). However, several questions remain regarding their role as regulators of gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…The impact, if any, of expression of AKR1D1 on CREB3L2 is unknown. In general, bidirectional promoters lack TATA boxes, are both GC-rich and enriched in CpG islands, and have an overrepresented set of motifs, including GABPA, MYC, E2F1, E2F4, NRF-1, CCAAT, YY1, and ACTACAnnTCC (12). GABPA, E2F1 and CCAAT motifs are present in the region between +1 of CREB3L2 and +1 of the AK058142 trancsript.…”
Section: Discussionmentioning
confidence: 99%
“…The most likely proposed function of such clustering is to coregulate two adjacent genes by a single bidirectional promoter. However, coexpression of two adjacent head-to-head genes does not occur much more often than would be expected by chance (7,8). Thus, head-to-head clustering might have other regulatory roles.…”
mentioning
confidence: 90%